Functional organization of the kdp genes of Escherichia coli K-12. - Rhoads, D B (1978)
The kdp genes code for a high-affinity and repressible K+ transport system. The regulation and organization of the kdp genes were analyzed by studies of constitutive mutants and of strains in which bacteriophage lambda is integrated into the kdp genes. The polar effects of lambda integration demonstrate that three of the kdp genes form an operon, kdpABC, read from A to C. The kdpD gene is a separate transcription unit and is the site of mutations making expression of the kdp genes partially constitutive. The constitutive mutants are dominant to kdpD+ in diploids. These findings, the fact that kdpD mutations identified previously are Kdp-, and the existence of intracistronic complementation between some kdpD mutations indicate that the kdpD gene product is an oligomeric positive regulator of the kdp genes. Deletions extending clockwise from kdp as far as the gltA locus were isolated from strains with bacteriophage lambda integrated into kdpD. Plaque-forming transducing lambda phages carrying the kdpABC operon were isolated.